The Effectiveness of "NAVIGASI DIRI": Smart Internet Self-Regulation-Based Intervention on Internet Addiction in Adolescents - Setyawan, Imam; Masykur, Achmad Mujab (Jurnal Psikologi, 2022)
This study aimed to examine the effectiveness of smart internet self-regulation-based intervention, the ‘NAVIGASI DIRI’, in reducing internet addiction in adolescents. The subjects of this study were 40 teenagers (16 girls, 24 boys) from a high school in Semarang, Central Java, Indonesia. The group intervention was carried out in five face-to-face sessions effectively for eight hours. The psychological scales that were compiled as a data collection tool were the Internet Addiction Scale (20 items, α = .843) and Self-Regulation Scale (25 items, α = .808). The experimental design used was pretest-posttest without control group design. The paired sample t-test on pretest and posttest data showed a significant decline in the level of internet addiction, t(39) = 2.640, p < .05, from pretest (M = 28.93; SD = 18.713) to posttest (M = 24.08; SD = 17.006). Meanwhile, the subjects’ self-regulation increased significantly, t(39) = -2.181, p < .05, from pretest (M = 71.85; SD = 6.192) to post-test (M = 73.40; SD = 6.250). The results of the simple regression test showed a moderate negative relationship between the two variables (r = -.548, p < .001; b = -1.490; t(38) = -4.035, p < .001). The coefficient of determination (R2 = .300) indicated that 30% of students’ internet addiction was determined by their self-regulation. The NAVIGASI DIRI Intervention has been proven to be effective in increasing the level of self-regulation of students which contributes to reducing the level of internet addiction.